2013
DOI: 10.1038/labinvest.2012.172
|View full text |Cite
|
Sign up to set email alerts
|

Berberine represses DAXX gene transcription and induces cancer cell apoptosis

Abstract: DAXX is a multifunctional protein that regulates a wide range of cellular signaling pathways for both cell survival and apoptosis. Regulation of DAXX gene expression remains largely obscure. We recently reported that berberine (BBR), a natural product derived from a plant used in Chinese herbal medicine, downregulates DAXX expression at the transcriptional level. Here, we further investigate the mechanisms underlying the transcriptional suppression of DAXX by BBR. By analyzing and mapping the putative DAXX gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
(43 reference statements)
1
30
0
Order By: Relevance
“…of PDPK1/SP1/DNMT1/GAPDH of three independent experiments. cell growth and apoptosis, and through disrupting the association of SP1 binding to the DAXX gene promoter, BBR inhibited the DAXX promoter activity, thereby inducing human neuroblastoma cell apoptosis [45]. Another report observed that BBR suppressed hepatocellular carcinoma cell growth by upregulating miRNA-22-3p and downregulating the expression of SP1, thereby reducing the expressions of its downstream targets, CCND1, (cyclin D1), a oncogenic cell-cyclerelated protein and BCL2, an apoptosis-related protein [46].…”
Section: Discussionmentioning
confidence: 99%
“…of PDPK1/SP1/DNMT1/GAPDH of three independent experiments. cell growth and apoptosis, and through disrupting the association of SP1 binding to the DAXX gene promoter, BBR inhibited the DAXX promoter activity, thereby inducing human neuroblastoma cell apoptosis [45]. Another report observed that BBR suppressed hepatocellular carcinoma cell growth by upregulating miRNA-22-3p and downregulating the expression of SP1, thereby reducing the expressions of its downstream targets, CCND1, (cyclin D1), a oncogenic cell-cyclerelated protein and BCL2, an apoptosis-related protein [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown to possess anticancer activities against various types of cancer cells. Berberine can induce apoptosis and cell-cycle arrest of tumor cells (10)(11)(12)(13)(14). In this report, we studied the effect of berberine on glioblastoma cells in vitro and on tumor xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…DAXX is a multifunctional protein that regulates a wide range of cellular signaling pathways for cell survival and apoptosis [39], while DDIT3 plays a central role in endoplasmic reticulum stress and DNA damage response, by inducing cell cycle arrest and apoptosis [40]. …”
Section: Discussionmentioning
confidence: 99%